(untitled) (Journal of the College of Basic Education, 2022)
The history of the manuscripts of forensic sciences is related to the history of forensic sciences, and their emergence to their appearance and codification. The Prophet, may God bless him and grant him peace, had writers who wrote in his hands. In addition to transcribing the Qur’an, the hadith, which was forbidden to be transcribed at first, was being transcribed, for fear of mixing it with the words of God Almighty. Except for the matter of writing down the Noble Qur’an, all of this supports what we have said that the manuscripts of legal sciences date back to the history of the emergence of legal sciences, which is related to the revelation of the first verse on the Prophet Muhammad, may God bless him and grant him peace, and among those manuscripts valuable in interpretation: ( Jama’at al-Tibyan fi tafsir al-Qur’an), which is considered one of the treasures of the ancient Islamic heritage, because it contains a statement of the Book of God Almighty, an explanation of its meanings, a statement of its vocabulary, and an explanation of its implications.